The influence of fluid ingestion on performance of soccer players during a match - Guerra, Isabela; Chaves, Rodrigo [UNESP]; Barros, Turibio; Tirapegui, Julio (My University, 2004)
The purpose of this study was to verify the effects of a carbohydrate-electrolyte drink on soccer performance. Twenty soccer players volunteered to participate in the study. Players were allocated to two assigned trials according to their positional roles in the team: CHO group (ingesting a 6% carbohydrate-electrolyte solution at regular 15 minutes intervals) and NCHO (ingesting no fluid) during 75 min on-field soccer game. During the trials, body mass loss, heart rate, time spent running, number of sprints and core temperature were measured. There were statistically significant changes (p < 0.05) in body mass loss (CHO: 1.14 ± 0.37 kg vs. NCHO: 1.75 ± 0.47 kg) and number of sprints performed (CHO: 14.70 ± 4.38 vs. NCHO: 10.70 ± 5.80) between groups. The main finding of the present study indicates that supplementation with a carbohydrate-electrolyte drink during a soccer match is beneficial in helping to prevent deterioration in performance. © Journal of Sports Science and Medicine (2004).
Keywords: Carbohydrate; Core temperature; Heart rate; Soccer performance; Sports drink